2013
DOI: 10.1016/j.jhsa.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Ligament Length and Carpal Diastasis During Wrist Flexion–Extension and After Simulated Scapholunate Instability

Abstract: Purpose To determine the role of the carpal ligaments during wrist flexion/extension and to understand if maintaining integrity of only the dorsal scapholunate ligament is adequate for maintaining stability of the scapholunate joint. Methods This study combined motion analysis and manual digitization of ligament attachment regions to generate predictions of carpal ligament length and implied strain during wrist motion and length changes after simulated ligamentous injury. Results Thirteen ligaments and 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…Nikolopoulos et al 63 reported a volar load to failure value of 86 N, which was roughly equal to that of the dorsal SLIL (83 N) at an elongation rate of 5 mm/min. The linear stiffness for the volar SLIL (32.8 N/mm) was greater than that of the dorsal SLIL (27.7 N/mm), which refutes the sectioning studies of Patterson et al 54 Logan et al 51 reported a volar load to failure of 125 N, which was actually twice that of the dorsal SLIL segment (62 N), but this was conducted at an elongation rate of 100 mm/min. Lee et al 64 used magnetic resonance imaging to measure the in vivo strain on the SLIL subregions when the wrist was axially loaded in extension to simulate a fall on an outstretched hand.…”
Section: Biomechanical Properties Of Slil Subregionssupporting
confidence: 72%
“…Nikolopoulos et al 63 reported a volar load to failure value of 86 N, which was roughly equal to that of the dorsal SLIL (83 N) at an elongation rate of 5 mm/min. The linear stiffness for the volar SLIL (32.8 N/mm) was greater than that of the dorsal SLIL (27.7 N/mm), which refutes the sectioning studies of Patterson et al 54 Logan et al 51 reported a volar load to failure of 125 N, which was actually twice that of the dorsal SLIL segment (62 N), but this was conducted at an elongation rate of 100 mm/min. Lee et al 64 used magnetic resonance imaging to measure the in vivo strain on the SLIL subregions when the wrist was axially loaded in extension to simulate a fall on an outstretched hand.…”
Section: Biomechanical Properties Of Slil Subregionssupporting
confidence: 72%
“…We defined the three regions of the SLIL according to their known bone insertions and marked the origin and insertion of these ligaments on the surfaces of the bone reconstructions [1,2,13,19,21] (Fig. 1).…”
Section: Image Reconstructionmentioning
confidence: 99%
“…Therefore, it is difficult to predict the movement of carpal bones after ligament lesions with imaging studies and clinical tests alone. 2 …”
Section: Introductionmentioning
confidence: 99%
“…It is believed that carpal instability is more common than previously thought and that degenerative disease is the end result of undiagnosed instability. 2 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation